Editorial [ Hot Topic: Current Methods and Perspectives in Biomarker Discovery (Guest Editors: Hans-Peter Deigner and Anna V. Baranova) ] - Deigner, Hans-Peter; Baranova, Ancha (Current Molecular Medicine, 2010)
As the “traditional” biomedical research efforts move us closer toward understanding why some people seem particularly vulnerable to one or another chronic disease, or why and how these diseases progress, the “translational” branch of the same field of science strives to develop molecular predictors for the course of the disease in given individual. These predictors are collectively known as biomarkers. More often than not, scientists inquiring about the mechanisms for particular human pathology serendipitously unearth a novel predictor, thus, venturing into the translational research and continue to moonlight in the biomarker area until the value of a novel biomarker for the bedside is proven or otherwise. Hence the root of the common belief holds the value of biomarker as somewhat proportional to its functional meaning within the pathogenetic realm of the disorder of interests. Contrary to this belief, many valuable biomarkers have no known function or their properties cannot be linked to underlying pathology without considerable speculative leap. In fact, even for the best-performing biomarkers, for example, carcinoembrionic antigen (CEA), PSA or hsCRP, the connection to underlying pathology assumes “missing link” similar to that of an ancient Chinese test for diabetes involving ants crawling to the patient's urine. In case of the described diabetes test, the “missing link” is obviously the glucose; however, it took an untold number of centuries to figure this out. The “missing link” does not interfere with correct diagnosis, as urine ant test was accidentally executed and corroborated by modern techniques even in relatively recent times [1, 2]. Since the discovery and the beginning of an industrial production of insulin, a great number of novel biomarkers for this disease have been introduced, but only few of these maintain direct connection to the pathogenesis (i.e. insulin and glucose levels in patient's blood). The best diabetic marker, HbA1c, had been chosen by American Diabetes Association (ADA) as the definitive test to diagnose diabetes, outperforming both the fasting plasma glucose test and the less commonly used oral glucose tolerance test [3]. Is there any particular role for HbA1c in diabetes pathogenesis? The answer is “No”. HbA1c is a simple sentinel that dutifully reports an extent of the damage done by unchecked glucose to the patients’ body. This marker is minimally invasive and cheap. Moreover, it delivers positive and negative predictive values superior to that of functionally important biomarkers. This wonderful biomarker was first discovered in the typical scientific “fishing expedition” of 1958, when it was first separated from other forms of hemoglobin using a chromatographic column [4]. Later, a serendipitous discovery of Rahbar revealed a substantial increase in its content in the samples of the blood taken from diabetic subjects [5, 6]. Since then, these two convoluted approaches, a “fishing expedition” and “serendipitous discovery”, provide for an unreliable road to success in biomarker discovery. An example of HbA1c illustrates that “biological plausibility” is not a prerequisite for any biomarker and certainly not an obstacle for successful future development. However desirable, truly biology-driven biomarker discovery would require a full understanding of a biological system including kinetics of interactions between its components, a “systems biology” vision we still are very far away from. Having that in mind, one should not be surprised to see that recent worldwide increases in funds allocated to the search for more biomarkers have not yet produced a breakthrough in the future of individualized medicine, but rather a promising trickle of the leads requiring an extensive validation. The biomarker discovery remains to be slow and often frustrating, even as the advent of genomics and related fields has dramatically accelerated this effort. In this issue we collected a number of important manuscripts either outlining recent efforts in the rationalization and the optimization of the biomarker discovery (Luchini et al., Sikaroodi et al. and Kohl, Current Molecular Medicine, this issue) or summarizing state-of-the-art in certain clinical areas desperately thirsty for the minimally invasive breakthroughs (Seli et al., Estep et al., Belousov et al., Claus et al. and Bonaterra et al., Current Molecular Medicine, this issue). Thus, this issue of “Current Molecular Medicine” reflects both medical need and therapeutic perspective for new biomarkers as well as the recent developments of the technology that facilitates these discoveries. With regard to the biomarker molecules, the articles encompass a variety of the biochemical entities, including RNA, micro RNA, proteins and small metabolites. While the use of single markers was commonplace in the past, it is now increasingly evident that complex diseases require marker panels to adequately reflect the status of patients. Along with technological progress in systems biology and with increasing coverage and data integration, a combination of different types of biomolecules into comprehensive panels may help to finally herald an era of personalized medicine.